Defect classification in reciprocating compressor using acoustic emission technique / Sim Hoi Yin - Sim, Hoi Yin (2013)
Performance of reciprocating machines relies heavily on health condition of its moving components, most importantly the valve. Non-intrusive methods such as vibration or acoustic emission (AE) technique are preferable in valve failure diagnosis as they can provide earlier fault detection. In this study, a valve failure detection methodology is proposed by using the AE technique. Wavelet packet transform (WPT) is chosen as the signal processing method over continuous wavelet transform (CWT) and discrete wavelet transform (DWT). This is because WPT can overcome high computational time and high redundancy problem in CWT and capable of providing detailed analysis of high frequency components which is found feeble in DWT. The features of AE signal can be extracted by computing normalized WPT coefficients under different valve conditions and machine operating conditions through statistical method. Finally, a classifying strategy is proposed to discriminate the signal under different valve conditions. Vibration signal will serve as a reference in comparing the effectiveness of AE signal in valve failure detection.